First records of Trichoptera from Timor-Leste, including seven newly described species - Wells, Alice; Cartwright, David (Zootaxa, 2021)
Several collections of adults of the caddisfly order Trichoptera were studied from Timor-Leste, the nation-state comprising the eastern region of the island of Timor. The specimens represent ten families: Hydrobiosidae (2 species), Glossosomatidae (1 species), Hydroptilidae (3 species), Philopotamidae (5 species), Hydropsychidae (3 species), Polycentropodidae (1 species), Psychomyiidae (3 species), Xiphocentronidae (1 species), Lepidostomatidae (1 species), Leptoceridae (3 species). Among the 24 species listed, 16 were identified as established Southeast Asian species. Among these are two very widespread species, one extending further east to New Guinea, northern Australia, and New Caledonia and another that was described from Fiji. An additional seven species are newly described here: Ulmerochorema hatubuilico sp. nov., Hydroptila bellisi sp. nov. and H. aileuensis sp. nov., Chimarra lawaliu sp. nov., C. multidentata sp. nov., C. sameana sp. nov. and C. timorensis sp. nov. Hitherto, the genus Ulmerochorema Mosely was believed to be an Australian endemic. A xiphocentronid specimen could be identified to genus Drepanocentron only.